2020
DOI: 10.1111/imj.14680
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric nutritional risk index is associated with mortality in peritoneal dialysis patients

Abstract: Background: Malnutrition is one of the most common complications among dialysis patients. The Geriatric Nutritional Risk Index (GNRI) is rarely used in dialysis patients, especially peritoneal dialysis (PD).Aim: To use the GNRI to evaluate the initial nutritional state of PD patients and to examine the association between the GNRI and mortality in chronic PD patients. Methods:We retrospectively examined the medical records at our centre to identify all adults (≥18 years) who had undergone PD for over 3 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Four-hour dialysate/plasma creatinine ratio is used as an indicator of peritoneal permeability ( 29 ). The Geriatric Nutritional Risk Index (GNRI) is an indicator of nutritional status calculated by (14.89 × serum albumin [g/dL]) + 41.7 × (body weight/ideal body weight [kg]) ( 30 ). Blood parameters and PD fluid parameters were measured by the Department of Clinical Laboratory, Saitama Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…Four-hour dialysate/plasma creatinine ratio is used as an indicator of peritoneal permeability ( 29 ). The Geriatric Nutritional Risk Index (GNRI) is an indicator of nutritional status calculated by (14.89 × serum albumin [g/dL]) + 41.7 × (body weight/ideal body weight [kg]) ( 30 ). Blood parameters and PD fluid parameters were measured by the Department of Clinical Laboratory, Saitama Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that the CONUT score, PNI, and GNRI had significant relationship with clinical outcomes including mortality and cardiovascular disease in PD patients. [12][13][14] In this study, we detect that a high CONUT score (.3) and low PNI (#40.2) are significant independent predictor of TF (especially early TF) in PD patients even after adjustment for covariates including gender, early peritonitis, BMI, diabetes, triglyceride, HDL-C, and EF. Besides, ROC curves indicate that PNI and CONUT score have better predictive value than GNRI.…”
Section: Discussionmentioning
confidence: 55%
“…In the published literatures, the Geriatric Nutritional Risk Index (GNRI), Prognostic Nutritional Index (PNI), and Controlling Nutritional Status (CONUT) score were independent predictors for allcause mortality in PD patients. [12][13][14] To our knowledge, only the CONUT score was found to be a reliable prognostic marker of TF. 14 The prognostic value of PNI and GNRI is still unclear.…”
Section: Introductionmentioning
confidence: 65%
“…Another study with a large Japanese cohort also demonstrated that a low/medium GNRI was related with all-cause mortality [16]. The relationship between the GNRI and mortality has been also validated in patients on PD and in those with NDD-CKD [18,19,21]. A recent meta-analysis further confirmed the findings of earlier studies reporting that a high GNRI could reduce the risk of all-cause mortality and that a lower GNRI was related with higher mortality in patients on dialysis [2].…”
Section: Utility Of Gnri As a Simple Nutritional Assessmentmentioning
confidence: 90%
“…Geriatric nutritional risk index (GNRI), which is based only on body weight, height, and serum albumin level, has been recently demonstrated as a very simple and objective tool to assess nutritional status in various pathological conditions [7,8]. Until now, several studies have examined the credibility of GNRI in assessing malnutrition and predicting all-cause mortality and cardiovascular (CV) events in patients on chronic hemodialysis [2,[8][9][10][11][12][13][14][15][16], peritoneal dialysis (PD) [17][18][19], non-dialysis-dependent (NDD) chronic kidney disease (CKD) [20,21], stroke [22][23][24][25], and heart failure [26][27][28].…”
Section: Introductionmentioning
confidence: 99%